دراسة تحليلية لالتهاب الحويضة و الكلية عند الأطفال (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة (50)  طفلاً, شخص لديهم مرض التهاب حويضة وكلية حاد(APN ). وكانت إصابة الإناث أعلى من الذكور,  (84%) من المرضى كانوا يعانون من ترفع حروري, و(20 %) من المرضى وجدت لديهم أعراض بولية سفلية, وكان المتوسط الحسابي  للبروتين الارتكاسي الالتهابي ( C RP ) ((55.6مغ/ دل, تعداد الكريات البيضاء في فحص  البول الأولي كان وسطيا( .5  44) كرية بالساحة, الاشريكية الكولونية شكلت (88.2%) من الجراثيم المسببة للمرض.  بعد  إجراء  الدراسات الشعاعية ( 46%) من المرضى وجد لديهم  تشوهات  بالطرق البولية . العلاج الوريدي و الفموي كانا متكافئان من حيث  الفعالية . 50 patients with acute pyelonephritis (APN) were included in this study. Females had had this disease more than males,. 84% of patient had high temperature and 20% of all patients developed symptoms of infection in the lower urinary tract. C-reactive protein (CRP) was almost ( 55.6) mg\dl. White blood cells in the primary  urine test  were about (44.5) cells. Escherichia coli was 88.2% of bacteria causing this disease. After doing X-rays  to all patients, 46% had abnormalities in the urine tract. The parenteral and oral treatments were equal in efficacy.